THE PROTECTION AFFORDED TO WELL-KNOWN TRADEMARKS IN SRI LANKA: A CRITICAL ANALYSIS - Thilakarathna, K.A.A.N. (GENERAL SIR JOHN KOTELAWALA DEFENCE UNIVERSITY, 2018)
A trademark which helps to distinguish goods of one undertaking from that of another is an important stimulus for manufacture of goods and services. In particular when it comes to well-known trademarks, the value attached to the mark exceeds the total value of assets of such an undertaking. A strong protection for these trademarks are required to protect the interest of the owners of these trademarks. The Intellectual Property Act No 36 of 2003 governs the law relating to the protection of both trademarks and well-known trademarks. As a member state to the TRIPS agreement, Sri Lanka is obliged to meet the minimum standards set out in the TRIPS agreement regarding the protection afforded to intellectual property rights in order to enjoy the benefits granted by the agreement. This paper is aimed at answering the questions of,what is the current status of the law relating to the protection of well-known trade marks in Sri Lanka, its international obligations, protections afforded to wellknown trademarks through exclusive and additional measures, the limitations of the current system and some possible reforms that could be made. The research is conducted using a qualitative method, where it uses the primary legal sources of the Intellectual Property Act No 36 of 2003, the Trips Agreement and the decided case law. As secondary data, it uses the commentaries given on the relevant sections by reputed authors.The results of the research indicate that, most of the provisions of the IP Act are compatible with the TRIPS agreement. However, the results also indicate that, with regard to the protection of well-known trademarks there are some lacunas, such as unregistered marks not having exclusive rights, nonregistrability of sound marks and the non-availability of a single application process for multiple registration in different countries. It is therefore suggested that these lacunas be remedied.
Keywords: Intellectual Property, Trademarks, Well- Known Trademarks, TRIPS, IP Act No 36 of 2003